Blockchain: A mechanism of “unorthodox” trust - Grigoriadou, Valentini (Homo Virtualis, 2019)
Blockchain is a revolutionary technology which is expected to cut off proxies, reduce cost and increase speed and range. It offers transparency, safety and traceability and considerable high levels of trust. In contrast with traditional hierarchical structures and central data-bases where trust lies within institutions, blockchain’s trust is technology. It could possibly constitute the core of a new type of internet. The fact that it is developing rapidly in various fields simultaneously, will inevitably change the way of communication in the future. Although, since its onset, it was mainly used for financial exchange; it becomes evident that it is applicable in every form of exchange. Thus the new digital trust through encryption could have a determining role in redeveloping higher education. In such a context, students, instructors and teachers are in direct relationship with one another; as a result new forms of interaction are generated. The main objective is to examine on the one hand blockchain’s application in the educational sector, focusing on its potential to change educational mechanisms for the better and on the other hand its reception and the influence this technology could have on the socio-psychological reality of the involved subjects. Its application on the field of education will undoubtedly be beneficial but it is an imperative that we inspect any potential dangers as well. Since people have the need of an institution that they can trust, the creation of a world of decentralised trust is a challenge.